Assessment of indoor air quality and thermal comfort in Portuguese secondary classrooms: methodology and results - Pereira, Luísa Dias (2014)
This work shows the results of a field study about indoor thermal comfort, based on investigations in Portuguese secondary schools' classrooms. The surveys herein presented were carried out in a school in Beja, in the South-East of Portugal. The field study was conducted by physical parameters monitoring and survey questionnaires. Both field monitoring and subjective surveys were performed at the same time during the regular class period (either at the end or at the beginning of the class). The measurement campaign consisted in measuring the environmental parameters – air temperature (Ta), air relative humidity (RH), CO2 concentrations. Outdoor air temperature values were registered hourly at the nearest climatological station. Through these data, along with the actual people clothing and metabolic rate being know, both Fanger's comfort indices were calculated (predicted mean vote and predicted percentage of dissatisfied people). The subjective survey investigated the thermal acceptability, the thermal sensation and the thermal preference. The judgments about the thermal environment were compared with the results of the field measurements. Draught preference votes, air stiffness and global air quality votes were also collected. The results show that the students found temperature range beyond the comfort zone acceptable, and revealed the occupants' accommodation to CO2 exposure, confirming the results obtained in other studies. Moreover, it was verified that running on naturally ventilation mode, CO2 concentration limits were highly exceeded.